Do New Urbanization Policies Promote Sustainable Urbanization? Evidence from China’s Urban Agglomerations - Shiwei Liu; Luyao Jia; Feng Zhang; Rutong Wang; Xian Liu; Lu Zou; Xuguang Tang (Land, 2024)
China’s urbanization has received as much attention as its economic growth in recent years. While rapid urbanization has promoted modernization and wealth creation, it has also brought many problems and challenges. So, since 2014, the Chinese government has implemented a new urbanization policy nationwide. However, few researchers have examined whether China’s new urbanization policies promote sustainable urbanization. This paper evaluates the sustainable urbanization of 19 urban agglomerations in China using the elastic coefficient. The results indicate a significant increase in the number of cities achieving sustainable urbanization since the implementation of China’s new urbanization policy. The number has risen from 46 in the period of 2010–2015 to 71 in the period of 2015–2021. Considering the impact of the new coronavirus on economy, there would have been even more cities entering sustainable urbanization during the latter period. This indicates that the new urbanization policy has a positive influence on the sustainable urbanization of China’s urban agglomerations. The sustainable urbanization status is not static and changes with different policies that are implemented in different time periods. Therefore, it is important to find useful policies that can guide and enhance the urbanization process in these cities. In addition, cities that have a sustainable urbanization status are not perfect. To address this issue, it is important to categorize and implement targeted policies for cities experiencing both sustainable and non-sustainable urbanization. Changes in a city’s size or urbanization rates are not related to the city’s sustainable urbanization status. A larger city size does not indicate sustainable urbanization, and, similarly, cities with faster urbanization rates do not exhibit a higher level of urbanization sustainability.